Network learning communities: Contributions to sustainability and integral training - Azólas Pérez, Katiuska; Saavedra González, Alejandra; Ubilla Riquelme, Mauricio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Sustainability implies a new way of understanding the world and organizing relationships. Based on values that tend to balance and human development, it installs the need to update educational models in Higher Education and become a contribution to sustainable development. In this context, the Bernardo O’Higgins University considers it necessary to compile those strengths of socio-constructivism and the dialogical model, as forms of relationship in and for community learning. Strengthening the analysis of comprehensive training from a qualitative approach. Realizing how processes improve when participating in spaces such as Network Learning Communities.